Primary Breast Lymphoma: A Rare but Important Differential Diagnosis in Patients with Breast Malignancy - Madabhavi, Irappa; Sarkar, Malay; Sagar, Raghavendra; Revannasiddaiah, Swaroop; Kumar, Vineet (South Asian Journal of Cancer, 2024)
This report is based upon the case of a young lady who presented with a history of a breast lump, which despite clinically resembling a carcinoma, was subsequently diagnosed to be a primary breast lymphoma (PBL). Though rare in incidence, PBL may masquerade as breast carcinoma. PBL accounts for about 1.7–2.2% of all extranodal non-Hodgkin's lymphoma, and is accountable for up to 0.5% of all breast malignancies. Given that the treatments of breast carcinoma and PBL are markedly different, it is very essential that core-biopsy be preferred in every patient being evaluated for carcinoma of the breast. The diagnosis of diffuse large B cell lymphoma (DLBCL) was confirmed by immunohistochemistry, and the patient has been treated with six-cycles of chemotherapy followed by involved field-radiotherapy to the right breast. After a year's follow-up, the patient remains free of disease.
Keywords: breast lymphoma; CHOP; chemotherapy; radiotherapy